Merkel cell polyomavirus DNA sequences in the blood of healthy population of Pakistan - Shahzad, Naveed; Hussain, Iqra; Gilani, Usman S; Tayyeb, Asima; Aslam, Muhammad A; Khurshid, Muhammad; Hassan, Umair; Tasneem, Fareeda; Umer, Muhammd; Rashid, Naeem (Future microbiology, 2019)
This study aimed at detecting and quantifying Merkel cell polyomavirus (MCPyV) viral loads in the peripheral blood of healthy Pakistani individuals. A total of 221 whole blood samples obtained from healthy individuals were examined by qPCR. MCPyV was detected in the peripheral blood of 31.2% healthy individuals. The rate of MCPyV positivity decreased from young (36%), to middle (33.7%) and elder (25.3%) age groups. Our data revealed higher prevalence of MCPyV in women (43.93%) than men (25.80%). The MCPyV viral load was calculated in the range of 0.06 -11 copies/ng of isolated DNA. The MCPyV viral load increased from young (median = 3.35) to elder (median = 5.66) age groups. The MCPyV circulate at a higher frequency by residing dormant in certain blood cells, which might act as potential vehicles for the spread of MCPyV infection among general population.